The effectiveness of using the new barcode system in Yamaha Electronics Manufacturing, Perak/ Shafiqa Shariman - Shariman, Shafiqa (2018)
The study that was carried out by the researcher is to find out the effectiveness of using the new barcode system in Yamaha Electronics Manufacturing, Perak. A total of 150 questionnaires has been distributed to the workers in Yamaha in order to collect the information. The respondents who were given the questionnaire are picked randomly in order to get the data. It is a stratified random sampling which has been chosen by the researcher. The questionnaires are of the primary data regarding the effectiveness of using the new barcode system. The independent variables obtain from past research that has been used for this research are technology, organization, people and also environment. The dependent variable which can be obviously seen is the new barcode system. The data collected is then analyze by the researcher to get the final result that supports and answers the research objective. A few test conducted in order to get the final result which can support the most suitable variable. There is a significant relationship between the technology and the new barcode system. For the other variable which is the organization, people and environment, alternative hypothesis is rejected. The researcher can conclude that the effectiveness of using the new barcode system is influenced by the technology used for the new barcode system.